2013
DOI: 10.9790/0837-1568189
|View full text |Cite
|
Sign up to set email alerts
|

TV Commercials and Choice of Food among Children in Sabah, Malaysia

Abstract: This study examines the relationships between television (TV) advertising and patterns of food choice among children. This relationship is crucial in understanding the intricate interplay among several interrelated variables such as TV viewing, preference for certain foods and the problem of obesity. Specifically, the study investigates the degree

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our study in urban Kuala Lumpur confirmed a reproducible pattern of children’s TV viewing time compared to a previous Malaysian study conducted in Sabah state [ 8 ]. During weekends, approximately 44 % children watched more than 3 h per day of TV compared to fewer hours during weekdays [ 8 ]. In our study, self-reported TV viewing time indicated 191 children (47.5 %) spent three hours or more watching TV daily (Table 3 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study in urban Kuala Lumpur confirmed a reproducible pattern of children’s TV viewing time compared to a previous Malaysian study conducted in Sabah state [ 8 ]. During weekends, approximately 44 % children watched more than 3 h per day of TV compared to fewer hours during weekdays [ 8 ]. In our study, self-reported TV viewing time indicated 191 children (47.5 %) spent three hours or more watching TV daily (Table 3 ).…”
Section: Discussionsupporting
confidence: 85%
“…Within this matrix of determinants, the social psychology cluster inclusive of television (TV) watching and media availability is influential at the societal level. In this environment, it is well understood that TV food advertising (TVFA) is the most dominant medium to promote unhealthy foods and food choices to young viewers [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nowadays, social media have become a powerful advertising and marketing medium targeted at children, (Potvin Kent et al, 2019). Thus, it influences children's consumption of fast food, which has led to the rise in obesity cases, (Totu et al, 2013).…”
Section: Advertisement and Marketingmentioning
confidence: 99%
“…Several variables affect fast-food intake. This is apparent from studies were undertaken by Grier et al (2007), Garber & Lustig (2011), Totu et al (2013) and Tim, Beevi & Yeap (2014). These reports also clarified several of the critical causes that have led to fast-food intake.…”
Section: Introductionmentioning
confidence: 99%